2019
DOI: 10.1155/2019/3476826
|View full text |Cite
|
Sign up to set email alerts
|

Smith Predictor‐Taylor Series‐Based LQG Control for Time Delay Compensation of Vehicle Semiactive Suspension

Abstract: A Smith predictor-Taylor series-based LQG (STLQG) control to compensate time delay of a semiactive suspension system is newly presented. This control consists of a Taylor series-based LQG (TLQG) control and a Smith predictor based on the TLQG. The TLQG control compensates one half of time delay to decrease magnification from whole time delay compensation. The Smith predictor based on the TLQG compensates the other half to decrease horizontal shift from whole time delay compensation using the Smith predictor-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As the key to achieve adaptive performance of MR intelligent suspension, the design of control algorithm in MR intelligent suspension research is the core issue. A series of control algorithms are proposed by researchers, including skyhook control algorithm [6], LQR control algorithm [7,8], neural network control algorithm [9,10], fuzzy control algorithm [11,12], robust control [13], human simulated intelligent control algorithm [14] and PID control algorithm [15,16] and so on. These algorithms usually take the absolute velocity of the sprung mass and relative velocity of the damper as the feedback variables of the controller, and the absolute velocity are obtained by acceleration integral.…”
Section: Introductionmentioning
confidence: 99%
“…As the key to achieve adaptive performance of MR intelligent suspension, the design of control algorithm in MR intelligent suspension research is the core issue. A series of control algorithms are proposed by researchers, including skyhook control algorithm [6], LQR control algorithm [7,8], neural network control algorithm [9,10], fuzzy control algorithm [11,12], robust control [13], human simulated intelligent control algorithm [14] and PID control algorithm [15,16] and so on. These algorithms usually take the absolute velocity of the sprung mass and relative velocity of the damper as the feedback variables of the controller, and the absolute velocity are obtained by acceleration integral.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation and experiment showed that the control algorithm could improve the vibration damping performance of the vehicle well. Tao et al [15] proposed a Smith predictor-Taylor series-based LQG (TLQG) control method to compensate the time delay of a semi-active suspension system. The time delay was divided into two parts, one half of which was compensated with a TLQG controller, and the other was further compensated by a TLQG-based Smith predictor.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yue Zhu and Sihong Zhu [13] developed a quartervehicle suspension equipped with an MR damper with a time delay using an adaptive neural network structure. Laihua Tao et al [14] applied a Smith predictor-Taylor seriesbased LQG control to compensate for the time delay of a vehicle's semi-active suspension. Young-Tai Choi et al analyzed MR dampers [15] and developed the controller for the landing gear system of a helicopter equipped with MR dampers.…”
Section: Introductionmentioning
confidence: 99%